A model of organisational learning based on control. (1st January 1999) - Templeton, Gary; Snyder, Charles
This paper generates a new theoretical model on the role of technology in organisations by focusing on the role of knowledge in theories about organisational learning and control. Literature reviews of both fields yield evidence that the two concepts are highly related, and that a new, extended paradigm for organisational thought is needed. An integrative control model is then presented as the manner by which organisations process knowledge, which accounts for a large amount of the scope of organisational knowledge management. The proposed model can help managers and researchers understand the many salient issues associated with the behaviour of knowledge in organisations.